The Effects of Poor Neonatal Health on Children's Cognitive Development - Figlio, David; Guryan, Jonathan; Karbownik, Krzysztof; Roth, Jeffrey (American Economic Review, 2014)
We make use of a new data resource–merged birth and school records for all children born in Florida from 1992 to 2002–to study the relationship between birth weight and cognitive development. Using singletons as well as twin and sibling fixed effects models, we find that the effects of early health on cognitive development are essentially constant through the school career; that these effects are similar across a wide range of family backgrounds; and that they are invariant to measures of school quality. We conclude that the effects of early health on adult outcomes are therefore set very early.